The Influence of Perfectionism, Academic Pressure, and Fear of Failure on the Stress Levels of Generation Z Students in the Era of Academic Competition - Adelia, Mairani; Daulay, Aqwa Naser; Nurbaiti, Nurbaiti (Jurnal Sains Sosio Humaniora, 2026)
This study aims to analyze the influence of perfectionism, academic pressure, and fear of failure on the stress levels of Generation Z students at the Faculty of Islamic Economics and Business, North Sumatra State Islamic University (FEBI UINSU). The study employed a quantitative approach with an associative research design. Data were collected through Likert-scale questionnaires distributed to respondents selected using purposive sampling techniques. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results showed that partially, perfectionism had a negative and significant effect on student stress, while academic pressure and fear of failure had a positive and significant effect on student stress. Simultaneously, all three variables also had a significant effect on academic stress. These findings indicate that adaptive perfectionism can help students manage academic demands in a more structured manner, whereas academic pressure and fear of failure tend to increase students’ psychological burden. Therefore, students’ academic stress is influenced by how they respond to the academic demands and challenges they face. This study is expected to serve as a basis for formulating more effective academic stress management strategies and supporting student well-being in higher education environments.